2021
DOI: 10.1016/j.jfineco.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable investing in equilibrium

Abstract: We present a model of investing based on environmental, social, and governance (ESG) criteria. In equilibrium, green assets have negative CAPM alphas, whereas brown assets have positive alphas. Green assets' negative alphas stem from investors' preference for green holdings and from green stocks' ability to hedge climate risk. Green assets can nevertheless outperform brown ones during good performance of the ESG factor, which captures shifts in customers' tastes for green products and investors' tastes for gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
194
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,012 publications
(379 citation statements)
references
References 55 publications
14
194
0
Order By: Relevance
“…Comparing with extant research, we show that more recent data present green funds outperforming conventional peers, similar to Ibikunle [17]. These results are also in line with Pástor et al [25], given an external shock related to more regulation and screening of firms' sustainability, green assets will exhibit higher returns, due to stronger loadings on the omitted ESG priced factor, which will reflect positive and larger CAPM alphas.…”
Section: Single-factor Capm Regression Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Comparing with extant research, we show that more recent data present green funds outperforming conventional peers, similar to Ibikunle [17]. These results are also in line with Pástor et al [25], given an external shock related to more regulation and screening of firms' sustainability, green assets will exhibit higher returns, due to stronger loadings on the omitted ESG priced factor, which will reflect positive and larger CAPM alphas.…”
Section: Single-factor Capm Regression Resultssupporting
confidence: 89%
“…Moreover, large, well-known firms have likewise transformed their business toward sustainability, with many others opening branches focused on the renewable energy industry, and they can now pass through green funds' strict screenings. This setting, in turn, reconciles our results with Pástor et al [25]'s model: if ESG concerns exhibit a positive shock of sufficient strength, green assets outperform brown assets, despite having lower expected returns. Equilibrium asset prices adjust to ESG tastes and concerns by tilting market portfolio towards ESG investors taste.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Theoretically it can be shown that if certain stocks are shunned by a large group of investors, this should lead to higher expected returns for such stocks; see Pástor, Stambaugh, and Taylor (2020), Pedersen, Fitzgibbons, and Pomorski (2020), and Zerbib (2020), amongst others. Thus, the very act of excluding sin stocks can give rise to a sin premium, which can be interpreted as a reward for the reputational risk that is involved with holding sin stocks.…”
Section: Theoretical Argumentsmentioning
confidence: 99%